(3QSGdI aj GdaQGFVs - (3GdbQSgQj, GdbQTgQj, eMehOs ((3eOQSI bGQj , eOQSI TjN CafOjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf hGdUdGI Ydi fHjg bGd GdfHj (B" (3e (B" (3JYdehG GdaQGFV hYdehgG ddfGS aEfgG fUa GdYde , jHOC ef JQcg GdejJ HGdJLgjRs
(3BNQgG (B:s
(3Ch eOHQgG Ch eOHQgG eOHQgG Ch ef LQO hdGDg eYJbgG Ch eYJb eYJbgG hef edc PG eMQe QMeg YJb Ydjg ajchf hdGDg dg JeJs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdaQGFVs